Dimensions Of Islamic Education In The Prevention Bullying ; Assessing In an Effort of Character Building for Children In School - Qolbi Khoiri (Prodi PGSD FIP UNM, 2018)
Bullies assume that violence and intimidation are compatible to be applied as the problem solving to achive they wish. This encourages violence properties that will carry over into adulthood. Thus unwittingly making school or other educational institution as a training ground for potential thugs who would later become their profession adulthood. Widely accepted definition is that a state that the student is doing the bullying when a child repeatedly and at all times behave negatively to one or more other children. Here is a negative action when someone intentionally hurt or try to hurt, or make someone uncomfortable. The point is not directly implied in the definition of aggressive behavior. This can affect the character of the child to grow up, the character is moral and mental qualities that formation is influenced by congenital factors (natural) and environment (socialization or Education - nurture). Islam provides a potential explanation that has good character of human beings before birth, but this potential must be constantly nurtured through socialization and Islamic religious education in schools, while Islamic religious education should be done in a planned, systematic and measurable in order to prevent and deal with bullying behavior child.